2022
DOI: 10.3389/fimmu.2022.981285
|View full text |Cite
|
Sign up to set email alerts
|

Function and mechanism of histone β-hydroxybutyrylation in health and disease

Abstract: Histone post-translational modifications (HPTMs) are essential epigenetic mechanisms that affect chromatin-associated nuclear processes without altering the DNA sequence. With the application of mass spectrometry-based proteomics, novel histone lysine acylation, such as propionylation, butyrylation, crotonylation, malonylation, succinylation, glutarylation, and lactoylation have been successively discovered. The emerging diversity of the lysine acylation landscape prompted us to investigate the function and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 99 publications
0
18
0
Order By: Relevance
“…These clarify how BHB regulates gene expression, especially in relation to pathways that respond to oxidative stress. The effects of OHB boosted the expression of FOXO3A, catalase, and mitochondrial superoxide dismutase [24 ▪▪ ].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…These clarify how BHB regulates gene expression, especially in relation to pathways that respond to oxidative stress. The effects of OHB boosted the expression of FOXO3A, catalase, and mitochondrial superoxide dismutase [24 ▪▪ ].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Lysine β-hydroxybutyrylation is a newly identified PTM in histones and nonhistone proteins in eukaryotes, which links cellular metabolism to gene expression . Emerging evidence shows its association with metabolic diseases, cardiovascular diseases, diabetes, neuropsychiatric disorders, and cancers. , A recent study showed that lysine β-hydroxybutyrylation could improve stability of COVID-19 antibodies in cells . The OTS for genetic encoding of lysine β-hydroxybutyrylation into proteins has been established in both E. coli and mammalian cells with an Mb PylRS variant (C313 V and Y349F) …”
Section: Lysine Modificationsmentioning
confidence: 99%
“…103 Kbhb is catalysed by p300, while SIRT1 to SIRT3 and HDAC1 to HDAC3 remove Kbhb. 104 In addition, p300 could catalyze lysine propionylation (Kpr), butyrylation (Kbu), crotonylation (Kcr) in histones. 105,106 Histone lysine lactylation (Kla) is a novel histone mark which was first reported in 2019.…”
Section: Epigenetic Regulatory Mechanismsmentioning
confidence: 99%